COMPARATIVE ANALYSIS OF TOLERANT ATTITUDES TOWARDS HEROES IN UZBEK AND RUSSIAN LITERATURE - Zhuraeva Mashkhura Kodirovna (Sciental Journals Publishing, 2025)
This article examines the role of gender tolerance in Uzbek and Russian literature through the analysis of characters in the works of Chulpon, Qadiriya, Dostoevsky and Pushkin. The main attention is paid to how literary images affect the formation of public ideas about gender roles. The article emphasizes the importance of literature in the discussion and rethinking of gender stereotypes and suggests ways to use literary analysis for the development of gender Tolerance.
Keywords: Gender tolerance, Uzbek literature, Russian literature, literary analysis, social stereotypes, gender roles.